Bracon hebetor say, 1836 (Hymenoptera: Braconidae: Braconinae),a parasitoid of stored rice in Malaysia - Aman, A.Z.; Yaakop, S. (Pusat Sistematik Serangga ,UKM, 2013)

(untitled)
A preliminary monitoring was done at a selected rice storage warehouse which has been infested by insect pests. Many individuals of braconid wasps that were observed during the monitoring process are believed to have the potential as parasitoids of the stored insect product. A species of braconid wasp, Bracon hebetor Say has been identified from the warehouse parasitizing Sitotroga cereanella Olivier